2016
DOI: 10.1017/s0022377816001124
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in astrophysical plasma turbulence from solar wind observations

Abstract: This paper summarises some of the recent progress that has been made in understanding astrophysical plasma turbulence in the solar wind, from in situ spacecraft observations. At large scales, where the turbulence is predominantly Alfvénic, measurements of critical balance, residual energy and three-dimensional structure are discussed, along with comparison to recent models of strong Alfvénic turbulence. At these scales, a few per cent of the energy is also in compressive fluctuations, and their nature, anisotr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
228
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(253 citation statements)
references
References 139 publications
(334 reference statements)
24
228
1
Order By: Relevance
“…SA perturbations above the limit (1) rapidly transfer their mechanical energy from the largest scales to plasma microscales and thermal energy, without the help of a turbulent cascade. This paradigm is at odds with standard theories of Alfvénic turbulence in collisionless systems [11], and may be crucial for understanding turbulent energy dissipation in astrophysical plasmas ranging from the intracluster medium (ICM) [12][13][14][15] to hot accretion flows [16] and high-β regions of the solar wind [5,[17][18][19].…”
mentioning
confidence: 99%
“…SA perturbations above the limit (1) rapidly transfer their mechanical energy from the largest scales to plasma microscales and thermal energy, without the help of a turbulent cascade. This paradigm is at odds with standard theories of Alfvénic turbulence in collisionless systems [11], and may be crucial for understanding turbulent energy dissipation in astrophysical plasmas ranging from the intracluster medium (ICM) [12][13][14][15] to hot accretion flows [16] and high-β regions of the solar wind [5,[17][18][19].…”
mentioning
confidence: 99%
“…The reason is that high-β, weakly collisional plasmas are susceptible to several kinetic instabilities when |∆p/p| 1/β, such as the firehose (Rosenbluth 1956;Chandrasekhar et al 1958;Hellinger & Matsumoto 2000) and mirror (Barnes 1966;Hasegawa 1969;Southwood & Kivelson 1993;Hellinger 2007) instabilities. These instabilities regulate the pressure anisotropy to values near the instability thresholds, an effect that has been diagnosed in various kinetic particle-in-cell simulations (Kunz et al 2014;Riquelme et al 2015;Hellinger & Trávníček 2015;Melville et al 2016) and directly observed using in situ measurements of particle distribution functions and magnetic fluctuations in the solar wind (Kasper et al 2002;Hellinger et al 2006;Bale et al 2009;Chen et al 2016;Chen 2016). Thus, as the magnitudes of pressure anisotropy (and thus parallel viscosity) specified by (1.4) are often unphysically large in weakly collisional, high-β plasmas, any fluid model of the fluctuation dynamo must adopt some form of microphysical closure to account for the otherwise absent regulation of the pressure anisotropy.…”
Section: (Compiled On 24 March 2020)mentioning
confidence: 89%
“…Several mechanisms may contribute to the nonadiabatic temperature profile of the solar wind. For instance, the plasma may be heated as a result of instabilities and turbulent fluctuations that extract energy from the streaming motion and convert it into kinetic energy of particles (e.g., Richardson & Smith 2003;Cranmer et al 2007Cranmer et al , 2009Chen 2016;Vech et al 2017;Tang et al 2018;Berčič et al 2019;Verscharen et al 2019a,b;López et al 2019;Shaaban et al 2019;Vasko et al 2019;Roberg-Clark et al 2019). The analysis of such local instabilities, however, does not allow for a definitive prediction of the global radial temperature profile.…”
Section: Introductionmentioning
confidence: 99%